Advertising and public relations research - Jugenheimer, Donald W.; Kelley, Larry D.; Hudson, Jerry; Bradley, Samuel D. (M.E. Sharpe, 2014)
Designed to serve as a comprehensive, primary text for research methods courses in Advertising and/or Public Relations programs, this new edition of features several new chapters as well as deeper content in existing areas based on feedback from students, instructors and practitioners.